Spatial and Temporal Variability of Extreme Hydroclimatic Events in the Bani River Basin - Fousseini Kouyaté; François Kossi Guédjé; Assane Ndiaye; Orou Moctar Ganni Mampo (Hydrology)
Severe hydroclimatic events affect ecosystems and human livelihoods, creating significant challenges for managing water resources. This study analyzed the rainfall and river flow trends in the Bani River Basin (BRB) from 1991 to 2020. Using indices such as the maximum rainfall over a one-day period (RX1DAY), maximum rainfall over a five-day period (RX5DAY), rainfall exceeding the 95th percentile (R95P), simple daily precipitation intensity (SDII), and peak discharge (Qmax), the modified Mann–Kendall test and Pettitt’s test were applied to assess the trends and identify potential breakpoints. The results revealed spatial variability, with southern regions showing reduced rainfall, while northeastern areas exhibit increasing extreme rainfall and river flow. The RX5DAY declined significantly after 2000, reflecting reductions in prolonged rainfall events, followed by the RX1DAY, which declined significantly after 2012, indicating a reduction in short-duration extremes. In contrast, the R99P, SDII, and Qmax exhibited positive trends, indicating intensifying rainfall intensity and extremes in discharge. A notable breakpoint was detected in 1993, marking a transition to increased extreme flows. The highest values of the rainfall indices (R95P, R99P, RX1DAY, RX5DAY, SDII) were concentrated in the southern part of the basin, while the north recorded lower values. These results highlight the basin’s vulnerability to climate variability and provide insights into hydroclimatic changes, serving as a basis for informed decision-making and future research.